2020
DOI: 10.1039/c9cs00893d
|View full text |Cite
|
Sign up to set email alerts
|

Topological two-dimensional polymers

Abstract: The structural topology of a 2D network defines its electronic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 54 publications
2
102
0
Order By: Relevance
“…In this sense, theoretical calculations are found to be very useful to predict or rationalize the relationships between chemical structural modifications and the properties of the resulting materials. DFT calculations on the electronic structures of different 2D conjugated polymers have been previously reported, with an emphasis on the role played by the network topology, [29][30][31] lattice symmetry 32 or structural differences between 1D and 2D, [33][34][35] among other structural factors. [36][37][38][39] However, while isolated truxene-based molecules have been amply theoretically explored, a systematic study of their 2D conjugated polymers has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, theoretical calculations are found to be very useful to predict or rationalize the relationships between chemical structural modifications and the properties of the resulting materials. DFT calculations on the electronic structures of different 2D conjugated polymers have been previously reported, with an emphasis on the role played by the network topology, [29][30][31] lattice symmetry 32 or structural differences between 1D and 2D, [33][34][35] among other structural factors. [36][37][38][39] However, while isolated truxene-based molecules have been amply theoretically explored, a systematic study of their 2D conjugated polymers has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We noticed that many 2D COFs with C3 symmetry form Kagome lattice, such as N3-COF mentioned earlier, and they display flat bands near the Fermi level arising from non-bonded states, which are adverse to the in-plane charge transport and will increase the effective mass of excitons as well. [43][44] Instead, COFs in Lieb lattice with C2 symmetry constructed by four-arm nodes lack flat bands near the Fermi level (Figure S1), and the effective mass of charge carriers and excitons is reduced and further modulated by tailoring chemical building blocks of COFs. Besides, D-A design usually leads to space-separated electrons and holes, namely enlarged exciton radius, so we propose to design conjugated D-A COFs in Lieb lattice utilizing donor unit as node and acceptor unit as edge, which will reduce not only band gaps but also exciton binding energies of COFs.…”
Section: Understanding Photoelectrochemical Processes In Cof-based Photocatalysts For Efficient Water Splittingmentioning
confidence: 99%
“…When node units with C3 symmetry are used to construct COFs in Kagome lattice, flat bands typically appear at the VBM or CBM (Figure S1 and Figure S21). [43][44] These flat bands are formed by non-bonding orbitals of node and edge units and have very large effective mass of electron or hole, which could lead to intriguing magnetic phenomenon but is not desired for high-performance charge transport. 43 Since the effective mass of exciton could be defined as 1/m * =1/me * +1/mh * , 42 where me * and mh * stand for the effective mass of electron and hole respectively, the flat band at VBM or CBM could also give rise to large exciton mass and binding energy.…”
Section: Modulating Band Gaps and Band Edge Energies In Cofs For Overall Water Splitting Under Visible Lightmentioning
confidence: 99%
“…During the two recent decades, profound new schemes of carbon nanostructures have been uncovered. [ 1 ] Carbon‐based systems range from C60 to single‐wall carbon nanotubes, and from graphite to graphene. [ 2–4 ] Technological properties of these materials are promising, they also exhibit different kinds of allotropes in each dimension: a (0D) fullerene molecule, (1D) nanotubes, (2D) graphene nanoribbons, and (3D) diamond.…”
Section: Introductionmentioning
confidence: 99%